2008
DOI: 10.1186/1476-4598-7-87
|View full text |Cite
|
Sign up to set email alerts
|

ALDH isozymes downregulation affects cell growth, cell motility and gene expression in lung cancer cells

Abstract: Background: Aldehyde dehydrogenase isozymes ALDH1A1 and ALDH3A1 are highly expressed in non small cell lung cancer. Neither the mechanisms nor the biologic significance for such over expression have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 64 publications
6
116
2
Order By: Relevance
“…Moreb et al 35 recently reported that the knock-down of ALDH1A1 and ALDH3A1 resulted in decreased proliferative activity of lung adenocarcinoma cell lines. Since the level of ALDH did not affect the proliferative activity of Hodgkin lymphoma cell lines in the present study, the effect of ALDH may differ among cancer cell types.…”
Section: Relationship Between Ros-low and Aldh-high Populationsmentioning
confidence: 99%
“…Moreb et al 35 recently reported that the knock-down of ALDH1A1 and ALDH3A1 resulted in decreased proliferative activity of lung adenocarcinoma cell lines. Since the level of ALDH did not affect the proliferative activity of Hodgkin lymphoma cell lines in the present study, the effect of ALDH may differ among cancer cell types.…”
Section: Relationship Between Ros-low and Aldh-high Populationsmentioning
confidence: 99%
“…ALDH isozymes including ALDH1A1, are important for multiple biological activities including drug resistance [25][26]. We have demonstrated that the uptake of TPT in cells exposed to an ALDH inhibitor (disulfiram) is enhanced (unpublished; data not shown).…”
Section: Extended Modelmentioning
confidence: 84%
“…4) In regard to ALDH, results reported to date appear to be complicated. Its enzymatic activity has been demonstrated in SCLC and NSCLC cells by the Aldefluor assay, as well as by a spectrophotometrical assay [92][93][94][95][96][97]. On the other hand, an immunohistochemical analysis using antibodies against ALDH1A1 and ALDH3A1 in tissue sections of surgical specimens of lung cancer demonstrated the expression of these ALDH isozymes in NSCLC cases, but not in SCLC cases, suggesting that the ALDH protein expression was limited to CSCs in NSCLC [96].…”
Section: Brief Summary Of Lung Csc Markers and Potential Problemsmentioning
confidence: 99%
“…One important issue to be addressed is which ALDH isozymes are responsible for the ALDH activity used to identify stem cell progenitors. Several studies have demonstrated that ALDH activity is needed for the differentiation of primitive progenitors into mature cells, thus fulfilling one of the defining characteristics of multipotent stem cells, and some lines of evidence suggest that ALDH1A1 is an important marker of hematopoietic stem cell progenitors [92]. In fact, ALDH1A1 is one of the enzymes involved in the production of retinoic acid from retinol, and retinoic acid is considered significantly important in maintaining a balance between hematopoietic stem cell selfrenewal and differentiation [92].…”
Section: Brief Summary Of Lung Csc Markers and Potential Problemsmentioning
confidence: 99%
See 1 more Smart Citation